Rola nabłonka barwnikowego siatkówki w patogenezie cukrzycowego obrzęku plamki i jego leczeniu - Chmielewska, Katarzyna; Robaszkiewicz, Jacek; Kosatka, Mariusz (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
Pigment epithelium-derived factor (PEDF) has recently been shown to be the most potent inhibitor of angiogenesis in the mammalian eye, suggesting that loss of PEDF is involved in the pathogenesis of proliferative diabetic retinopathy. However, a protective role for PEDF in pericyte loss requires elucidation. Present studies suggest that PEDF proteins could protect against advanced glycation end product (AGE), which induce injury in retinal pericytes. Substitution of PEDF proteins may be a promising strategy in the treatment of patients with early diabetic retinopathy. Therefore, injury of RPE is the basic condition, not only of the progress of neovascularization, but initiation of early diabetic microangiopathy and macular edema as well. Recently new intravitreal drugs being used in the treatment of eye diseases with increased level of VEGF. Intravitreally administered a human, monoclonal anti-VEGF agent acts only as symptomatic treatment. It does not eliminate hypoxia and requires repeated administration. It is worth emphasizing, that VEGF functions are not limited to active angiogenesis, but also seems to require the maintenance and differentiation of mature blood vessels, such as the choriocapillaris. Therefore, delivery of these anti-VEGF treatments needs to be specific to sites of neovascularization or limited to a short duration, to prevent disruption of the normal vasculature. The effective method, which preserves RPE, improves oxygenation and release traction on the macula, leading to decreased permeability with subsequent resolution in DME, is pars plana vitrectomy with ILM peeling. There are several investigations that support the theoretical value of vitrectomy for the treatment of DME. Intraoperative administration of anti-VEGF agent and corticosteroids may additionally improve results of operative treatment.